Answer:
a=28
Step-by-step explanation:
use inverse operations
<u>TO FIND :-</u>
<u>FORMULAES TO KNOW BEFORE SOLVING :-</u>
<u>SOLUTION :-</u>
1) θ = 16°
Length of side opposite to θ = 7
Hypotenuse = x
≈ 25.3
2) θ = 29°
Length of side opposite to θ = 6
≈ 12.3
3) θ = 30°
Length of side opposite to θ = x
Hypotenuse = 11
4) θ = 43°
Length of side adjacent to θ = x
Hypotenuse = 12
≈ 8.8
5) θ = 55°
Hypotenuse = 6
≈ 3.4
6) θ = 73°
Length of side adjacent to θ = 8
≈ 27.3
7) θ = 69°
Length of side opposite to θ = 12
≈ 4.6
8) θ = 20°
Length of side opposite to θ = 11
≈ 30.2
(2.8, 0.8)
(0.8, -1.8)
1. Home (Xa, Ya)= (8, 6)
San Antonio (Xb, Yb)=(-5, -7)
Xa-Xb=8-(-5)=13
Ya-Yb=6-(-7)=13
Emily starts at 2/5 of the road, make it (Xc, Yc)
Xc= Xa-(Xa-Xb)2/5=8-5.2=2.8
Yc=Ya-(Ya-Yb)2/5=6-5.2=0.8
=> Emily starts at (2.8, 0.8)
2.
Emily ends at 3/5 of the road, , make it (Xd, Yd)
Xd= Xa-(Xa-Xb)3/5=8-7.8=0.8
Yd=Ya-(Ya-Yb)3/5=6-7.8=-1.8
=> Emily ends at (0.8, -1.8)
4
1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40
x = 3, x = 0
To solve these factored equations, just divide each part by zero and solve.
2x(x-3) = 0 → (x-3) = 0, and 2x = 0.
(x-3) = 0 → x - 3 + 3 = 0 + 3 → <u>x = 3.</u>
2x = 0 → 2x/2 = 0/2 → <u>x = 0.</u>